Azides and Porphyrinoids: Synthetic Approaches and Applications. Part 1—Azides, Porphyrins and Corroles - Araújo, Ana R. L. (Molecules, 2020)
Azides and porphyrinoids (such as porphyrin and corrole macrocycles) can give rise to new derivatives with significant biological properties and as new materials’ components. Significant synthetic approaches have been studied. A wide range of products (e.g., microporous organic networks, rotaxane and dendritic motifs, dendrimers as liquid crystals, as blood substitutes for transfusions and many others) can now be available and used for several medicinal and industrial purposes.